Evidence for the involvement of IL-1β and TNF-α in anti-inflammatory effect and antioxidative stress profile of the standardized dried extract from Miconia albicans Sw. (Triana) Leaves (Melastomataceae). (15th September 2020) - Lima, Tamires C.; Matos, Saulo S.; Carvalho, Thaís F.; Silveira-Filho, Alex J.; Couto, Luzi P.S.M.; Quintans-Júnior, Lucindo J.; Quintans, Jullyana S.S.; Silva, Ana Mara O.; Heimfarth, Luana; Passos, Fabiolla R.S.; Gandhi, Sathiyabama R.; Lima, Bruno S.; et al.
Abstract: Ethnopharmacological relevance: Miconia albicans (Melastomataceae), commonly known in Brazil as "canela-de-velho", is used in folk medicine for treating rheumatoid arthritis and reducing pain and inflammation. The aim of the current work was: to provide data on physicochemical characterization of the drug plant and dried extract from M. albicans leaves, as well as investigate the anti-inflammatory effect and antioxidant stress profile from the standardized dried extract of this species employing different model systems. Materials and methods: plant material (dried crushed leaves) was extracted by turboextraction using 50% ethanol (v/v). Different pharmacological techniques were performed to establish quality control parameters of the plant drug, and dried extract of M. albicans (DEMA) was chemically characterized by HPLC-PDA to selection of the chemical marker. Total phenolic and flavonoid contents were determined by the Folin-Ciocalteu and AlCl3 colorimetric methods, respectively. Antioxidant potential of the DEMA was investigated by employing different in vitro antioxidant assays, including DPPH and ABTS radical scavenging assays, ferric reducing antioxidant assay, NO scavenging assay, metal ion (Fe 2+ ) chelating activity and antioxidant capacity by inhibition of lipid peroxidation (TBARS). Finally, anti-inflammatory activity of the DEMA was evaluated using two models of acute inflammation: carrageenan induced inflammation and mechanical hyperalgesia. Results and discussion: M. albicans leaves, after drying in forced air circulation chamber at ±40 °C for 48 h and crushing in knife mill, presented a moisture content below the maximum allowed for plant drugs (6.4%). The powder of M. albicans was classified as moderately coarse and total ash content was found to be 6.27%. Preliminary phytochemical screening of DEMA revealed the presence of flavonoids, tannins, saponins, leucoanthocyanins and steroids. DEMA had significant higher total phenolic (551.3 mg gallic acid equivalent/g of dried extract) and flavonoid contents (367.19 mg catechin equivalent/g of dried extract). Two major compounds (λ = 340 nm) were identified in DEMA by HPLC-PDA: the flavonoids rutin and quercetin. Rutin content, selected as chemical marker, was determined and found to be 1.16 mg/g dried extract (r = 0.9941). Regarding to antioxidant activity, our results revealed the DEMA exhibited good antioxidant activity on different models. M. albicans treatment also reduced the levels of TNF-α e IL-1β and consequently inflammatory nociception and edema caused by carrageenan injection. Based on previous studies and our results, is possible to suggest a positive correlation between the flavonoids rutin and quercetin and the antioxidant and anti-inflammatory capacities. Conclusion: Together, these data suggest that M. albicans has the possibility of use in conditions such as arthritis or other joint pain, even needing other work to better consolidate this profile.